ORTHOSTATIC REACTIONS OF VENTRICULAR RATE IN PATIENTS WITH PERMANENT ATRIAL FIBRILLATION - Fomych, G. M.; Yabluchanskiy, N. I.; Martimyanova, L. A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
A relationship between different types of orthostatic reactions (OR) of ventricular rate (VR) and clinical manifestation of permanent atrial fibrillation (AF) in 73 patients (32 men and 41 women) aged (55 ± 15) years with a prescription AF (6 ± 5) years has been studied. All types of OR have been noticed in studied population. Positive OR of VR have been dominated (41 %), negative and absent OR of VR have been occurred more rarely (34 % and 25 % respectively). Qualified positive OR of VR have been occurred in 27 %, and negative – 40 % of patients. High incidence of prognostically less favorable qualified negative, positive and absent OR of VR in elderly and senile patients with AF requires closer attention with more precise examination, drug therapy and lifestyle modification of patients.